Dictionary as an Instrument of Ideology: Anarchism in the Context of Lexicographic Publications of the Soviet Period - M Yu Martynov (RUDN Journal of Language Studies, Semiotics and Semantics, 2013)
The paper considers the analysis of political lexicon in the dictionaries of the Soviet period. The author shows that the lexicographic treatment of the words “anarchism” and “power” isn’t neutral, it is caused by the hidden ideology, real political opposition of marxism and anarchism after 1917.